CHEMICAL AND ENERGETIC CHARACTERIZATION OF Eucalyptus grandis × Eucalyptus urophylla CLONES SUBJECT TO WIND DAMAGE - Zanuncio, Antonio José Vinha; Carvalho, Amélia Guimarães; Carneiro, Angelica de Cassia Oliveira; Colodette, Jorge Luiz; Rocha, Maria Fernanda Vieira (Revista árvore, 2019)
ABSTRACT Wind damages are common in forest plantations and the use of this wood can minimize losses. The objective was to evaluate the chemical composition and the energetic potential of wood and charcoal from trees subject to wind damage. Eight (A to H) two-years-old Eucalyptus grandis × Eucalyptus urophylla clones were selected in a region where wind damage is frequent. The basic density, calorific value, chemical composition of wood and calorific value, immediate chemistry and gravimetric yield of charcoal were determined for all clones. Materials with high lignin content and low S/G ratio had higher gravimetric yield. The energy density of wood and charcoal showed high relationship with the basic and apparent relative density, respectively. All materials showed potential for bioenergy, but the clone E stood out with higher gravimetric yield and energy density. RESUMO Danos por ventos são frequentes em plantações florestais, e a utilização desta madeira pode minimizar os prejuízos causados. O objetivo foi avaliar a composição química e o potencial energético da madeira e carvão de árvores sujeitas a danos pelos ventos. Oito clones de Eucalyptus grandis × Eucalyptus urophylla com idade de dois anos foram selecionados em região onde danos por ventos ocorrem com alta frequência. A densidade básica, poder calorífico, composição química da madeira e poder calorifico, química imediata e rendimento gravimétrico do carvão foram determinados para todos os clones. O rendimento gravimétrico de materiais com alto teor de lignina e baixa relação S/G foi maior. A densidade energética da madeira e carvão apresentou maior relação com a densidade básica e aparente, respectivamente. Todos os materiais apresentaram potencial para bioenergia, mas o clone E se destacou com alto rendimento gravimétrico e densidade energética.